Pengaruh Permainan Tradisional Dakon Terhadap Kemampuan Matematika Anak Usia 5-6 Tahun di PAUD Alam Anak Negeri - Tuti Alawiyah; Muhammad Muhajirin (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2026)
Early mathematical ability in early childhood is a crucial foundation for academic success at subsequent educational levels. However, field observations indicate that mathematics learning in early childhood education (PAUD) still tends to use conventional methods that are less engaging and meaningful for children. The traditional game of Dakon, as a unique local cultural heritage, has great potential to teach mathematical concepts naturally and enjoyably. This study aims to examine the effect of the traditional Dakon game on the mathematical abilities of children aged 5–6 years at PAUD Alam Anak Negeri. A quantitative approach was employed using a quasi-experimental research design with a one-group pretest-posttest design. The research subjects consisted of 25 children aged 5–6 years at PAUD Alam Anak Negeri. Data were collected through mathematical ability tests, including a pretest before the treatment and a posttest after the treatment. The instrument used was a structured observation sheet that had been tested for validity and reliability. Data were analyzed using a paired sample t-test with SPSS. The results showed a significant difference between the pretest scores (mean = 56.80) and posttest scores (mean = 82.40), with a two-tailed significance value of 0.000 (p < 0.05). The traditional Dakon game has a positive and significant effect on improving the mathematical abilities of children aged 5–6 years. This study recommends the use of the traditional Dakon game as an effective, enjoyable, and contextual mathematics learning medium.